1970
DOI: 10.1136/bmj.1.5696.596
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amoebic Meningoencephalitis in Britain

Abstract: Summary: Meningoencephalitis proved to be due to an amoeba (Naegleria) has been diagnosed in Great Britain for the first time. The first patient (a boy of 2) survived longer than any previously recorded cases, but in spite of early diagnosis and treatment he died 15 days after the onset of meningeal symptoms.Two other children who were exposed to the same possible source of infection (a warm, muddy puddle) had similar symptoms and developed mild meningitis. A naegleria was isolated from the cerebrospinal fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0
2

Year Published

1975
1975
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 14 publications
0
37
0
2
Order By: Relevance
“…AmB has been shown by several investigators (5,12,13) to be effective in protecting mice and other experimental animals from amoebic infection and, in spite of its potential toxicity, has promise in clinical treatment of humans suffering from primary amoebic meningoencephalitis (4,7,16). The occurrence of a reproducible set of ultrastructural changes in pathogenic amoebae may be useful in monitoring effectiveness of in vivo drug susceptibility in chemotherapeutic studies involving Naegleria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AmB has been shown by several investigators (5,12,13) to be effective in protecting mice and other experimental animals from amoebic infection and, in spite of its potential toxicity, has promise in clinical treatment of humans suffering from primary amoebic meningoencephalitis (4,7,16). The occurrence of a reproducible set of ultrastructural changes in pathogenic amoebae may be useful in monitoring effectiveness of in vivo drug susceptibility in chemotherapeutic studies involving Naegleria.…”
Section: Resultsmentioning
confidence: 99%
“…The major application for AmB has been against systemic fungal infections, but it also has activity against protozoans (22,27). In recent years, amoebae of the genus Naegleria have been shown to be susceptible to AmB (4,6,15,16), a point of particular interest since these organisms are capable of invading the central nervous system of humans, causing an almost invariably fatal meningoencephalitis. This study has examined the effects of AmB on growth and ultrastructure of some representative strains of free-living and pathogenic Naegleria spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the in vitro and in vivo activity of amphotericin B against various strains of N. fowleri (5-8, 13, 17, 19, 20, 21), and at least seven patients with primary amebic meningoencephalitis have been successfully treated with amphotericin B alone or in combination with other drugs (1,2,14,16,19,25).…”
mentioning
confidence: 99%
“…PAM, caused by free-living amoebae of the genus Naegleria, usually results in death; of the approximately 80 documented cases, there have been only three survivors (1,2,6). Many different antimicrobial agents (and treatment regimens) have been used to treat PAM, but the most promising appears to be the antifungal polyene, AMB.…”
mentioning
confidence: 99%